I Am Not in Your Shoes: Low Perspective Taking Mediating the Relation Among Attachment Insecurities and Physical Intimate Partner Violence in Chilean University Students. Issue 22 (November 2018) - Lafontaine, Marie-France; Guzmán-González, Mónica; Péloquin, Katherine; Levesque, Christine
Guided by the attachment theory, this study tested the degree to which perspective taking mediates the effects of romantic attachment on the use of physical intimate partner violence (IPV) toward the partner. Participants consisted of 608 Chilean university students involved in a romantic relationship, among whom 44.2% of women and 34.7% of men reported inflicting at least one act of violence toward their partner during the previous year. Results from a structural equation model showed that the association between avoidance of intimacy and physical IPV is mediated by perspective taking for both men and women. However, perspective taking mediated the link between attachment anxiety and physical IPV in women only. Our findings underline the importance of the individual's sense of attachment security in relation to their ability to empathize with their partners, as well as prevent the perpetration of physical IPV against them.